Combined approach for far-lateral lumbar disc herniation - Ozveren, MF; Bilge, T; Barut, S; Eras, M (Japan Neurosurgical Soc, 2004)
This study evaluated the combination of the classical interlaminar approach and the intertransverse route through a midline approach for the treatment of 18 patients with far-lateral lumbar disc herniations, as identified by magnetic resonance imaging. The patients presented with acute severe sciatica, antalgic posture, positive Lasegue sign and femoral stretch test, motor and sensory deficits, and reflex loss findings. Discectomy of all 18 patients was performed by the combined approach. Neurological outcome of all patients was excellent in the follow-up period, ranging from 5 to 8 years. This combined midline approach permits complete evacuation of the involved disc level and treatment of additional bone resection procedures. Therefore, we advocate this approach in far-lateral lumbar disc herniation cases.
Keywords: Microsurgical Approach; Surgical-Management; Spinal Stability; Diagnosis